Studi Implementasi Program Kabupaten Layak Anak Studi di Kabupaten Pemalang Provinsi Jawa Tengah Tahun 2013 - Raharjo, Tri; ., Purwoko; Martini, Rina (Journal of Politic and Government Studies, 2015)
ABSTRAC In the district pemalang , is limited government policy to unite the issue of the right to development planning in the district , and not teritegrasinya the right to protection of children in the development district or city. The child is worthy of the district government policy which aims to collect pemalang government resources , the community , the family in the form of policy , institutional , the program and development activities aimed at fulfilling the right the right of children To uncover the problems the problems and research purposes , researchers used a type of research evaluation .Data analysis by evaluation is descriptive .The purpose of this research is to find program evaluation district worthy of children in district pemalang and evaluate factors driving and inhibitors of the district worthy of this kid .The data collection techniques that the author of use in this research is an interview and the study of literature . The results of research shows that the government district pemalang to toward pemalang worthy of children is pembentukkan task force team district worthy of the son of one of them is pembentukkan forum children become a bridge between the government with the village community .In its implementations policy based on research is considered good enough to see the implementation of variables in this policy .A factor that impedes from the program is a lack of coordination of a unit of local government work with the village children which results in lack of socialization of the forum of the child to existing community in village. Keyword: Deserving child district , the implementation of policy , forum child